THE DESCRIPTION OF STUDENTS’ ABILITY IN ORDERING ADJECTIVE ON DESCRIPTIVE TEXT MATERIAL AT THE SEVENTH GRADE OF UPTD SMP NEGERI 2 GUNUNGSITOLI UTARA IN 2022/2023 - selamat putra jayazega; Yasminar Amaerita Telaumbanua; Hasrat Sozanolo Harefa; Riswan Zega (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Writing descriptive is the activity to give an information to the other, which aims to describe things, people, places. Adjective order is included as the language feature on descriptive text material. Qualitative research method is the method that was used for this research. The focuses of this research was to find out the students’ ability in ordering adjective on descriptive text material and to determine the factors affecting the students’ ability in ordering adjective on descriptive text material. Furthermore, the informant of the research were 21 students of Class VII-C of UPTD SMP Negeri 2 Gunungsitoli Utara in 2022/2023. Then, the students’ worksheet and the interview sheets were the instruments that were used for the research. Based on the instrument, it was found that the students’ average got the score very poor (52%) and followed by poor score (48%), and no one of the students who achieved good or excellent score in ordering adjective. Furthermore, the factors of the students’ ability were caused by two factors, namely: factor of lacking of knowledge, and factor of lacking of vocabulary. After conducting the analysis, the ability of the students in class VII-C of UPTD SMP Negeri 2 Gunungsitoli Utara in ordering adjective were low. Then the factor influence the students’ ability in ordering adjective were lacking of knowledge and lacking of vocabulary. The teacher’s action is important to the students in increasing the students’ knowledge in learning English, particularly in adjective order.